Effect of Non-Structural Organics and Inorganics Constituents of Switchgrass During Pyrolysis - Kim, Pyoungchung; Hamilton, Choo; Elder, Thomas; Labbé, Nicole (Frontiers in Energy Research, 2018)
Non-structural components, such as inorganics and organic extractives, present in switchgrass were extracted with water and ethanol, and the resulting non-structural components-free materials were pyrolyzed to investigate the effect of the inorganic species on the pyrolytic products. The extraction was performed for switchgrass materials harvested from three consecutive growing seasons, removing 8.5 wt% of the organic extractives in the first season biomass, and 5.8 and 6.3 wt% in the second and third season, respectively, on total dry basis of biomass. In addition to organic extractives, from 0.7 to 2.7 wt% of ash were extracted. Specifically, 99% and 59% of total K and Mg were removed from the switchgrass harvested in the second and third growing season. Thermogravimetric analysis demonstrated that a predominant reduction of K and Mg content in the biomass increased temperature at which mass loss rate is maximized in the decomposition of cellulose, hemicellulose, and lignin. The reduction of K and Mg content also affected pyrolytic products generated at 450°C. The chromatographic peak area percentage of levoglucosan from the extracted samples in the second and third growing season was two to three times higher than that from the extracted samples in the first growing season, showing a strong negative correlation with K and Mg content, whereas most of the light oxygenated and furanic/pyranic/cyclopentanic products exhibited a strong positive correlation with K and Mg content. We concluded that the removal of non-structural components prior to thermochemical conversion processes such pyrolysis can potentially produce a valuable extractives stream while removing catalytic inorganics that negatively impact downstream pyrolysis process.